Talent management related concepts and debates in container shipping industry by an emerging market perspective - Ramazan Özkan Yildiz; Soner Esmer (Journal of Shipping and Trade (JST), 2021)
Talent management (TM) is referred as a young and developing field and it is claimed to be require more contribution from the different industry and country perspectives. Because of the highly dynamic and competitive nature of the container shipping industry, possession of valuable and unique human capital assets is evaluated as a substantial necessity to achieve business objectives and sustained competitive advantage by container shipping companies. Accordingly, TM is considered to be an essential factor contributing the accomplishment of these goals and the successful implementation of corporate strategy. Therefore, this study aims to contribute the development of TM field by investigating and evaluating TM related concepts and debates in Turkish container shipping industry. Through this extent, a combined method of content analysis with in-depth interview, has been organized to analyse TM oriented subjects in container shipping industry.
Keywords: 650; Talent; Talent management; In-depth interview; Qualitative contentanalysis; Container shipping industry